MAC layer congestion control techniques in vehicular ad hoc network: survey and qualitative analysis. (12th August 2020) - Sharma, Swati; Harit, Sandeep
Vehicular ad hoc network (VANET) has become a promising area in the research community because of its various applications in road safety, mobile infotainment, and traffic management. Each vehicle can exchange information regarding the current status of traffic flow and warning through vehicle to vehicle (V2V) and vehicle to infrastructure (V2I) mode of communication. There is a high need for reliable communication to reduce the number of accidents, and to enhance road safety. It can be ensured using efficient congestion control techniques at the medium access control (MAC) layer. The design of MAC layer protocols in VANET is a challenging task because of dynamic topology, frequent link breakage, limited bandwidth, and quality-of-service (QoS) requirements. In this paper, various congestion control schemes that are designed for the MAC layer of VANET are classified and discussed, which include time-division multiple-access (TDMA) and decentralised congestion control (DCC) techniques. TDMA MAC protocols divide the time into slots, and one vehicle can access the medium at each slot. DCC is a cross-layer function at each layer of the intelligent transportation system (ITS). This study discusses various benefits, limitations, and characteristics of the techniques mentioned above. Finally, a qualitative comparison is performed on different performance parameters.